The Effect of Cayyey Chill Formulation (Capsicum frutescens Linn) Against Cuko Pempek - Alhanannasir Alhanannasir; Mukhtarudin Muchsiri; Ade Vera Yani; Kiki Rizki Amelia; Nico Syahputra Sebayang (Politeknik Negeri Lampung., 2025)
Cuko is a black pempek sauce originating from South Sumatra Province made from cayenne pepper, garlic, tamarind, palm sugar and salt. This study aims to determine the level of spiciness of pempek cuko against the formulation of manik cayenne pepper, genie cayenne pepper and sekar cayenne pepper. The research was conducted in the Laboratory of the Faculty of Agriculture, Muhammadiyah University of Palembang, Testing Laboratory of the Bogor Agricultural Post-Harvest Instrument Standards Center from December 2023 to August 2024. The research method used a Randomized Block Design (RAK) arranged in a Non-Factorial manner with 7 treatments C1 (15 grams of manik cayenne pepper: 15 grams of genie cayenne pepper: 15 grams of sekar cayenne pepper), C2 (20 grams of manik cayenne pepper: 20 grams of genie cayenne pepper: 20 grams of sekar cayenne pepper), C3 (15 grams of manik cayenne pepper: 15 grams of genie cayenne pepper: 20 grams of sekar cayenne pepper), C4 (15 grams of manik cayenne pepper: 20 grams of genie cayenne pepper: 20 grams of sekar cayenne pepper) C5 (20 grams of manik cayenne pepper: 15 grams of genie cayenne pepper: 20 grams of sekar cayenne pepper) C6 (20 grams of manik cayenne pepper: 20 grams of genie cayenne pepper: 15 grams of cayenne pepper sekar) C7 (20 grams of cayenne pepper manik: 15 grams of cayenne pepper genie: 15 grams of cayenne pepper sekar). The parameters observed included chemical analysis of vitamin C levels and Capsaicin levels. The results showed that the effect of cayenne pepper formulation on cuko pempek had no significant effect on vitamin C and Capsaicin levels. The highest vitamin C levels were found in treatment C2 with an average of 30.988% and the lowest vitamin C levels were found in treatment C1 with an average of 30.102%. The highest Capsaicin levels were found in treatment C5 with an average of 41.4% and the lowest Capsaicin levels were found in treatment C1 with an average of 24.61%. The results of the hedonic test on color, aroma, and taste had a significant effect on cuko pempek